Glass fiber composite packaging adhesive film as well as preparation method and application thereof

By using glass fiber composite packaging film, the problem of thermal expansion mismatch of perovskite battery packaging materials is solved, and higher battery stability and service life are achieved.

CN119529685APending Publication Date: 2025-02-28JIANGSU SAILBOAT PETROCHEMICAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411700017.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing perovskite battery packaging materials have high thermal shrinkage and thermal expansion coefficient, which leads to mismatching the thermal expansion of other components of perovskite battery, affecting the stability and service life of the battery.

Method used

A glass fiber composite encapsulation film is adopted, including a grafted modified polymer layer and a glass fiber cloth layer arranged in sequence, so that the lateral and longitudinal shrinkage rate of the adhesive film and the linear thermal expansion coefficient in the thickness direction are reduced by this structure.

Benefits of technology

It effectively reduces the thermal expansion mismatch problem of perovskite battery packaging materials, and improves the battery's high and low temperature alternation resistance and packaging stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529685A_ABST
    Figure CN119529685A_ABST
Patent Text Reader

Abstract

The invention provides a glass fiber composite packaging adhesive film as well as a preparation method and application thereof. The glass fiber composite packaging adhesive film comprises a first bonding layer, a middle layer and a second bonding layer which are sequentially stacked, the first bonding layer and the second bonding layer are graft modified polymer layers; and the middle layer is a glass fiber cloth layer. The composite packaging adhesive film provided by the invention is low in shrinkage rate and uniform in fluidity when the adhesive film is laminated, adhesive shortage caused by too slow flowing is avoided, and a perovskite battery is prevented from being extruded and damaged due to too fast flowing, so that water and oxygen are prevented from entering a battery piece to damage the battery piece in a use process caused by lamination defects; compared with a traditional thermoplastic polyolefin elastomer (POE) packaging adhesive film, the packaging adhesive film has the advantages that the thermal expansion coefficient is lower, the stretching or compression effect of out-of-plane strain caused by the adhesion effect in the thickness direction can be effectively reduced, and therefore the high and low temperature alternating resistance of the perovskite battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and relates to a glass fiber composite packaging film and a preparation method and application thereof, and specifically relates to a glass fiber composite packaging film for perovskite cells and a preparation method thereof. Background Art

[0002] As the global demand for renewable energy grows, solar cells are becoming more and more widely used as an important clean energy source. Among them, perovskite cells are considered to be one of the important development directions of the next generation of solar cells due to their high photoelectric conversion efficiency and low-cost potential. However, the performance of perovskite cells is affected by many factors, including the selection and design of packaging materials. Compared with traditional silicon crystal cells, the internal crystal structure of perovskite cells is relatively fragile and more sensitive to environmental factors such as water, oxygen, acid, heat, and chemical additives. Packaging materials with good sealing and stability are required to protect the battery structure from moisture, oxygen and other environmental factors. In addition, the packaging material also needs to have good thermal expansion matching with other components of the battery, such as the glass substrate and the perovskite battery layer, to ensure the stability of the battery under temperature changes.

[0003] Existing perovskite battery packaging technology mainly uses polyolefin elastomer (POE) as packaging film. This material can have good transparency, barrier properties, aging resistance and adhesion, etc., and can effectively protect the internal structure of the battery. However, this material has a high thermal shrinkage rate, and battery components are prone to defects during lamination. In addition, these materials have a high linear thermal expansion coefficient in the thickness direction, and there is a large thermal expansion mismatch problem with other components of the perovskite battery, such as the glass substrate and the perovskite battery layer. The adhesion of these materials in the thickness direction can cause the tensile or compression effect of the out-of-plane strain, especially when used in outdoor alternating hot and cold environments. This strain is more obvious, which may cause the perovskite battery material to rupture. In severe cases, the perovskite battery material may even be directly pulled off the glass substrate, thereby affecting the photovoltaic performance of the device.

[0004] That is, the existing perovskite battery packaging technology has the following main problems: First, the existing packaging materials, such as POE, have high shrinkage and thermal expansion coefficients, and there is a large thermal expansion mismatch problem with other components of the perovskite battery, such as the glass substrate and the perovskite battery layer, which may cause the battery to deform under temperature changes, affecting its stability and aging performance; secondly, the fluidity of the existing packaging materials is difficult to match the lamination temperature, which is easy to cause lamination defects. When the components are exposed to sunlight and air for a long time, water and oxygen may enter and damage the battery cells, affecting the service life of the battery.

[0005] There are many methods for reducing the thermal expansion coefficient of the perovskite film layer in the current public technology, such as adding high-boiling point sulfone additives (CN116406212A), chemical crosslinking agents (CN113285031A), and polymerized molecular monomers (CN115528178A) to the perovskite precursor solution. These methods have improved the thermal stability of the internal materials of the perovskite battery to a certain extent, but when the perovskite battery is encapsulated, the encapsulation film generally uses a thermoplastic polyolefin elastomer. This material has a high thermal shrinkage rate, and the battery components are prone to defects during lamination. In addition, the linear thermal expansion coefficient of the material in the thickness direction is high, and there is a large thermal expansion mismatch problem with other components of the perovskite battery, such as the glass substrate and the perovskite battery layer.

[0006] Therefore, in the art, it is desired to develop a packaging adhesive film which has low shrinkage in both the transverse and longitudinal directions and has suitable fluidity. Summary of the invention

[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a glass fiber composite packaging film and a preparation method and application thereof, and specifically to provide a glass fiber composite packaging film for perovskite cells and a preparation method thereof.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a glass fiber composite packaging adhesive film, the glass fiber composite packaging adhesive film comprising a first adhesive layer, an intermediate layer, and a second adhesive layer stacked in sequence;

[0010] The first adhesive layer and the second adhesive layer are both graft-modified polymer layers;

[0011] The middle layer is a glass fiber cloth layer.

[0012] The composite encapsulation film provided by the present invention has a glass fiber cloth layer in the middle layer and grafted modified polymer layers on both sides, which increases the contact area between the glass fiber and the polymer material, and is conducive to better interface bonding and stability between the two. The organizational structure of the glass fiber cloth serves as a continuous skeleton of the composite encapsulation film, and can firmly grasp the polymer, thereby achieving low lateral and longitudinal shrinkage rates of the composite encapsulation film. This continuity can also make the overall performance of the composite encapsulation film uniform, and the effect brought about is difficult to achieve by filling with conventional inorganic fillers.

[0013] Preferably, the materials of the first adhesive layer and the second adhesive layer independently include a silane coupling agent graft-modified polymer or a maleic anhydride graft-modified polymer.

[0014] The material of the first adhesive layer is selected from a silane coupling agent grafted modified polymer or a maleic anhydride grafted modified polymer. The obtained encapsulation film is used for perovskite cells, which can not only achieve the bonding of the first adhesive layer with the perovskite cell layer, but also increase its bonding strength with the glass fiber, reduce the internal defects of the composite film, and further reduce the linear expansion coefficient of the composite film. In addition, the grafting polymer method avoids the problem of easily destroying the perovskite crystal layer by simply adding small molecule silane or maleic anhydride.

[0015] Preferably, the melting points of the silane coupling agent grafted modified polymer or the maleic anhydride grafted modified polymer are independently 60 to 90°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc. If the melting point is too high, the packaging temperature needs to be increased accordingly, and high temperature is easy to damage the perovskite battery; but if the melting point is too low, the packaging film will be difficult to transport and store, and the creep will be serious after the packaging is used.

[0016] Preferably, the silane coupling agent grafted modified polymer includes any one of silane coupling agent grafted modified polyolefin elastomer, ethylene propylene diene monomer rubber (EPDM), ethylene propylene diene monomer rubber (EPM), polyisobutylene (PIB), and amorphous α-olefin copolymer (APAO) or a combination of at least two thereof.

[0017] Preferably, the silane coupling agent includes any one of mercaptosilane, epoxysilane, aminosilane, methacryloxysilane, vinylsilane, and isocyanatesilane, or a combination of at least two thereof.

[0018] Preferably, the maleic anhydride grafted modified polymer includes any one or a combination of at least two of maleic anhydride grafted modified polyolefin elastomer, ethylene propylene diene monomer rubber (EPDM), ethylene propylene diene monomer rubber (EPM), polyisobutylene (PIB), and amorphous α-olefin copolymer (APAO).

[0019] Preferably, in the silane coupling agent grafted modified polymer or the maleic anhydride grafted modified polymer, the grafting rate of the silane coupling agent or maleic anhydride is independently 0.2-3%, for example, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, etc.

[0020] Preferably, the second adhesive layer also includes a light stabilizer. A light stabilizer can be added to the second adhesive layer. With the barrier of the middle glass fiber cloth layer, the light stabilizer is not easy to migrate to the surface of the adhesive film, reducing the damage of the light stabilizer to the perovskite layer.

[0021] Preferably, based on the total weight of the second adhesive layer as 100%, the content of the light stabilizer is 0-2.5%, for example 0 (i.e., no light stabilizer is added), 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, etc.

[0022] Preferably, the structure of the glass fiber cloth in the middle layer is any one of plain weave, twill weave, satin weave, rib weave or basket weave, and the gram weight of the glass fiber cloth is 50-500 g / m 2 , for example 50g / m 2 , 100g / m 2 , 150g / m 2 , 200g / m 2 , 250g / m 2 , 300g / m 2 , 350g / m 2 , 400g / m 2 , 450g / m 2 , 500g / m 2 The monofilament diameter of the fiber material of the glass fiber cloth is 5 to 20 μm, for example, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc.

[0023] Preferably, the thickness of the first adhesive layer is 10-150 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, etc.

[0024] Preferably, the thickness of the intermediate layer is 150-450μm, for example 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm, 300μm, 310μm, 320μm, 330μm, 340μm, 350μm, 360μm, 370μm, 380μm, 390μm, 400μm, 410μm, 420μm, 430μm, 440μm, 450μm, etc.

[0025] Preferably, the thickness of the second adhesive layer is 10 to 250 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, etc.

[0026] In the present invention, by limiting the thickness of each layer within a specific range, a relatively high glass fiber content can be maintained, which is an effect that cannot be achieved by filling with inorganic fillers, thereby reducing the linear thermal expansion coefficient of the adhesive film in the thickness direction. Using it for perovskite batteries can effectively solve the problem of thermal expansion mismatch between perovskite battery packaging materials and other component materials, and improve the battery's resistance to high and low temperature alternation.

[0027] Preferably, the transverse and longitudinal heat shrinkage rates of the glass fiber composite packaging film are both less than 5%, for example, 4.8%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1%, 0.5%, 0%, etc.

[0028] Preferably, the linear thermal expansion coefficient of the glass fiber composite packaging film in the thickness direction is less than 300 μm / (m·℃), for example, 280 μm / (m·℃), 240 μm / (m·℃), 220 μm / (m·℃), 200 μm / (m·℃), 150 μm / (m·℃), etc.

[0029] In a second aspect, the present invention provides a method for preparing the glass fiber composite packaging film as described in the first aspect, the preparation method comprising the following steps:

[0030] The grafted modified polymer is cast on both sides of the glass fiber cloth to obtain the glass fiber composite packaging adhesive film.

[0031] In a third aspect, the present invention provides an application of the glass fiber composite packaging film as described in the first aspect in a perovskite battery.

[0032] In specific use, the first adhesive layer faces the perovskite cell side, and the second adhesive layer faces the rear glass side.

[0033] The glass fiber composite packaging film provided by the present invention is used for perovskite cells, which mainly solves the following problems: 1) how to ensure the lamination packaging of perovskite cells while avoiding lamination defects caused by thermal shrinkage of the film, thereby avoiding water and oxygen from entering and damaging the battery cells during use; 2) how to reduce the linear thermal expansion coefficient of the packaging film in the thickness direction, reduce the tensile or compression effect of the out-of-plane strain caused by adhesion, and improve the high and low temperature alternating performance of the perovskite cell.

[0034] The glass fiber composite packaging film provided by the present invention can be widely used in the application fields of solar cell preparation, packaging material science, and organic-inorganic composite materials. With the growing global demand for clean energy, solar energy, as an unlimited and renewable energy source, has a very broad application prospect. As a new type of solar cell, perovskite solar cells have the advantages of high efficiency and low cost, and have received widespread attention and rapid development. The three-layer composite packaging film of grafted modified polymer layer / glass fiber cloth / grafted modified polymer layer provided by the present invention can effectively solve the problem of thermal expansion mismatch between perovskite battery packaging materials and other materials of the component, can improve the packaging stability of perovskite batteries and the high and low temperature alternating performance of battery components, and at the same time, the use of glass fiber cloth composite solution reduces the amount of POE material, reduces the cost of packaging material preparation, and can meet the needs of large-scale production and application.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The composite encapsulation film provided by the present invention has a low shrinkage rate and uniform fluidity during film lamination. It will neither flow too slowly to cause glue deficiency nor flow too fast to squeeze and damage the perovskite battery, thereby avoiding lamination defects that cause water and oxygen to enter during use and damage the battery cell.

[0037] (2) The present invention adopts a three-layer composite packaging film of grafted modified polymer layer / glass fiber cloth / grafted modified polymer layer. Compared with the traditional thermoplastic polyolefin elastomer (POE) packaging film, it has a lower thermal expansion coefficient and can effectively reduce the tensile or compressive effect of the out-of-plane strain caused by adhesion in the thickness direction, thereby improving the high and low temperature alternating performance of the perovskite battery.

[0038] (3) The preparation method of the present invention is simple and easy to implement. It not only improves the packaging stability of the perovskite battery, but also improves the high and low temperature alternating performance of the perovskite battery component, reduces the preparation cost, and meets the needs of large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1A This is the ultraviolet color rendering of the perovskite simulated battery provided in Example 1.

[0040] Figure 1B This is the ultraviolet color rendering of the perovskite battery simulation component provided in Example 1.

[0041] Figure 1C This is the ultraviolet color rendering of the perovskite battery simulation component provided in Example 1 after TC50.

[0042] Figure 2 The ultraviolet color rendering image of the perovskite simulated battery provided in Example 2 (left), the ultraviolet color rendering image of the perovskite battery simulated component (middle), and the ultraviolet color rendering image of the perovskite battery simulated component after TC50 (right).

[0043] Figure 3 The ultraviolet color rendering image of the perovskite simulated battery provided in Example 3 (left), the ultraviolet color rendering image of the perovskite battery simulated component (middle), and the ultraviolet color rendering image of the perovskite battery simulated component after TC50 (right).

[0044] Figure 4 The ultraviolet color rendering image of the perovskite simulated battery provided in Example 4 (left), the ultraviolet color rendering image of the perovskite battery simulated component (middle), and the ultraviolet color rendering image of the perovskite battery simulated component after TC50 (right).

[0045] Figure 5 The ultraviolet color rendering of the perovskite simulated battery provided for Comparative Example 1 (left), the ultraviolet color rendering of the perovskite battery simulated component (middle), and the ultraviolet color rendering of the perovskite battery simulated component after TC50 (right), wherein the small picture above the right picture is an enlarged picture of the black box area.

[0046] Figure 6 The ultraviolet color rendering image of the perovskite simulated battery provided for Comparative Example 2 (left), the ultraviolet color rendering image of the perovskite battery simulated component (middle), and the ultraviolet color rendering image of the perovskite battery simulated component after TC50 (right). DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] Example 1

[0049] In this embodiment, a glass fiber composite packaging adhesive film is provided, wherein the glass fiber composite packaging adhesive film comprises a first adhesive layer (with a thickness of 150 μm), an intermediate layer (with a thickness of 300 μm), and a second adhesive layer (with a thickness of 50 μm) which are stacked in sequence;

[0050] The materials of the first adhesive layer and the second adhesive layer are both silane coupling agent grafted modified polyolefin elastomer (wherein the polyolefin elastomer POE is LG company LF675, the silane coupling agent is Sibao Technology Company KH570, and the grafting rate is 0.2%), and the melting point is 75°C;

[0051] The middle layer is a glass fiber cloth layer, wherein the structure of the glass fiber cloth is plain weave and the gram weight is 300g / m 2 , the single fiber diameter of the fiber material is 5μm.

[0052] The preparation method comprises the following steps:

[0053] The silane coupling agent grafted modified polyolefin elastomer is cast on both sides of the glass fiber cloth to obtain the glass fiber composite packaging adhesive film.

[0054] The shrinkage rate of the glass fiber composite encapsulation film was tested in accordance with the Chinese photovoltaic industry standard T / CPIA0004-2017. The specific method was as follows: first, the light side of a 3.2 mm thick embossed glass was placed upward in an oven preheated to 120°C, and the temperature was controlled at 120°C. Then, the sample was flattened on the glass surface, heated for 3 minutes, taken out and cooled to room temperature, and the length (L, mm) and width (B, mm) at the minimum distance were measured. Then, the shrinkage rate was calculated according to the formula and recorded in Table 1.

[0055] The linear thermal expansion coefficient of the glass fiber composite packaging film in the thickness direction was tested according to ISO-11359-2-1999 standard (specific test conditions: heating rate: 5°C / min, test atmosphere: N2; gas flow rate: 50 mL / min; load: 0.05 N, temperature range: -40 to 30°C) and recorded in Table 1.

[0056] In this embodiment, a perovskite battery simulation component is also provided, and the preparation method includes the following steps:

[0057] (1) Coating 50 μm perovskite quantum dots (FAPbI3) on the glass surface to obtain a perovskite simulated battery, and then conduct a UV light color development test, observe the appearance, and take a photo to record as V1. Cut the above composite encapsulation film into a shape that matches the size of the perovskite simulated battery and set it aside.

[0058] (2) Cover the cut composite encapsulation film on the perovskite simulated battery to ensure complete coverage, and lay glass of the same size on the other side of the film to obtain a laminate.

[0059] (3) Place the laminate obtained in step (2) into a photovoltaic laminator, set the packaging temperature to 110° C., the pressure to 0.1 MPa, and the packaging time to 20 minutes.

[0060] (4) After the packaging is completed, the component is cooled to room temperature, the perovskite battery simulation component is taken out, and the packaging quality is checked to ensure that it is well sealed and has no bubbles or cracks.

[0061] (5) Subject the encapsulated perovskite battery simulation component to a UV light color development test, observe the initial appearance, and take a photo and record it as C1.

[0062] (6) The component of step (5) is subjected to 50 cycles of high and low temperature alternating aging (according to IEC61215 standard) (TC50), and then subjected to a UV light color development test, the appearance is observed, and a photo is taken and recorded as T1.

[0063] The ultraviolet color rendering image (V1) of the perovskite simulated battery provided in this embodiment is as follows: Figure 1A As shown, the UV color rendering of the perovskite battery simulation component (C1) is as follows Figure 1B As shown, the UV color image (T1) of the perovskite battery simulation component after TC50 is as follows Figure 1C shown.

[0064] Example 2

[0065] In this embodiment, a glass fiber composite packaging adhesive film is provided, wherein the glass fiber composite packaging adhesive film comprises a first adhesive layer (with a thickness of 10 μm), an intermediate layer (with a thickness of 450 μm), and a second adhesive layer (with a thickness of 10 μm) which are stacked in sequence;

[0066] The materials of the first adhesive layer and the second adhesive layer are both silane coupling agent grafted modified polyolefin elastomer (brand R1020, purchased from Coase, grafting rate 2%), and the melting point is 90°C;

[0067] The middle layer is a glass fiber cloth layer, wherein the structure of the glass fiber cloth is a mat pattern and the gram weight is 450g / m 2 , the single filament diameter of the fiber material is 20 μm.

[0068] The preparation method and testing method of the glass fiber composite packaging film and the preparation method of the perovskite battery simulation component are the same as those in Example 1.

[0069] The ultraviolet color rendering of the perovskite simulated battery provided in this embodiment (V2, left), the ultraviolet color rendering of the perovskite battery simulated component (C2, middle), and the ultraviolet color rendering of the perovskite battery simulated component after TC50 (T2, right) are shown in FIG. Figure 2 shown.

[0070] Example 3

[0071] In this embodiment, a glass fiber composite packaging adhesive film is provided, wherein the glass fiber composite packaging adhesive film comprises a first adhesive layer (with a thickness of 50 μm), an intermediate layer (with a thickness of 150 μm), and a second adhesive layer (with a thickness of 250 μm) which are stacked in sequence;

[0072] The materials of the first adhesive layer and the second adhesive layer are both maleic anhydride grafted modified polyolefin elastomer (wherein the polyolefin elastomer POE is LG Company's LF675, maleic anhydride is purchased from Aladdin, and the grafting rate is 3%), and its melting point is 68°C;

[0073] The middle layer is a glass fiber cloth layer, wherein the structure of the glass fiber cloth is satin and the weight is 150g / m 2 , the single filament diameter of the fiber material is 15 μm.

[0074] The preparation method and testing method of the glass fiber composite packaging film and the preparation method of the perovskite battery simulation component refer to Example 1.

[0075] The ultraviolet color rendering of the perovskite simulated battery provided in this embodiment (V3, left), the ultraviolet color rendering of the perovskite battery simulated component (C3, middle), and the ultraviolet color rendering of the perovskite battery simulated component after TC50 (T3, right) are shown in FIG. Figure 3 shown.

[0076] Example 4

[0077] In this embodiment, a glass fiber composite packaging adhesive film is provided, wherein the glass fiber composite packaging adhesive film comprises a first adhesive layer (with a thickness of 50 μm), an intermediate layer (with a thickness of 350 μm), and a second adhesive layer (with a thickness of 50 μm) which are stacked in sequence;

[0078] The materials of the first adhesive layer and the second adhesive layer are both maleic anhydride grafted modified polyolefin elastomer (wherein the polyolefin elastomer POE is LG Company's LF675, maleic anhydride is purchased from Aladdin, and the grafting rate is 1.5%), and its melting point is 60°C;

[0079] The middle layer is a glass fiber cloth layer, wherein the structure of the glass fiber cloth is ribbed and the weight is 350g / m 2 , the single filament diameter of the fiber material is 8 μm.

[0080] The preparation method and testing method of the glass fiber composite packaging film and the preparation method of the perovskite battery simulation component refer to Example 1.

[0081] The ultraviolet color rendering of the perovskite simulated battery (V4, left), the ultraviolet color rendering of the perovskite battery simulated component (C4, middle), and the ultraviolet color rendering of the perovskite battery simulated component after TC50 (T4, right) provided in this embodiment are shown in FIG. Figure 4 shown.

[0082] Comparative Example 1

[0083] In this comparative example, a packaging film is provided, the material of the packaging film is a polyolefin elastomer grafted with a silane coupling agent (wherein the polyolefin elastomer POE is LG's LF675, the silane coupling agent is KH570 from Sibao Technology Company, and the grafting rate is 0.2%), the melting point is 75°C, and the thickness is 500μm.

[0084] The preparation method comprises the following steps: preparing the packaging adhesive film by grafting a silane coupling agent onto a modified polyolefin elastomer through basic casting.

[0085] The testing method of the encapsulation film and the preparation method of the perovskite battery simulation component are the same as those in Example 1.

[0086] The ultraviolet color rendering of the perovskite simulated battery (DV1, left), the ultraviolet color rendering of the perovskite battery simulated component (DC1, middle), and the ultraviolet color rendering of the perovskite battery simulated component after TC50 (DT1, right) provided in this comparative example are as follows Figure 5 As shown, the small picture above the right picture is an enlarged picture of the black box area.

[0087] Comparative Example 2

[0088] In this comparative example, a packaging film is provided. The material of the packaging film is maleic anhydride grafted modified polyolefin elastomer (wherein the polyolefin elastomer POE is LG Company's LF675, maleic anhydride is purchased from Aladdin, and the grafting rate is 3%), the melting point is 68° C., and the thickness is 450 μm.

[0089] The preparation method comprises the following steps: preparing the packaging adhesive film by basic casting of maleic anhydride grafted polyolefin elastomer.

[0090] The testing method of the encapsulation film and the preparation method of the perovskite battery simulation component are the same as those in Example 1.

[0091] The ultraviolet color rendering of the perovskite simulated battery (DV2, left), the ultraviolet color rendering of the perovskite battery simulated component (DC2, middle), and the ultraviolet color rendering of the perovskite battery simulated component after TC50 (DT2, right) provided in this comparative example are as follows: Figure 6 shown.

[0092] Table 1

[0093]

[0094] It can be seen from Table 1 that the glass fiber composite packaging film provided by the present invention has a lower lateral shrinkage rate (0%) and a lower longitudinal shrinkage rate (0%-3%), and has a lower linear thermal expansion coefficient in the thickness direction (153-280μm / (m·℃)), and the perovskite battery simulation components prepared therefrom have no defects before and after aging.

[0095] Compared with Example 1, the encapsulation film provided in Comparative Example 1 has a higher longitudinal shrinkage rate and a higher linear thermal expansion coefficient in the thickness direction. After lamination, the perovskite in some areas is destroyed, the quantum yield disappears, and non-luminescent areas appear (such as Figure 5 ), after 50 cycles of high and low temperature alternating aging, a new damage area appears in the upper left corner (such as Figure 5 (enlarged image on the right).

[0096] Compared with Example 3, the transverse and longitudinal shrinkage rates of the encapsulation film provided in Comparative Example 2 are significantly increased, and the linear thermal expansion coefficient in the thickness direction is also significantly increased. The perovskite battery simulation component prepared therefrom has defects before and after aging.

[0097] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the glass fiber composite packaging adhesive film and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A glass fiber composite packaging film, characterized in that: The glass fiber composite packaging film comprises a first adhesive layer, an intermediate layer, and a second adhesive layer which are stacked in sequence; The first adhesive layer and the second adhesive layer are both graft-modified polymer layers; The middle layer is a glass fiber cloth layer.

2. The glass fiber composite packaging film according to claim 1, characterized in that: The materials of the first adhesive layer and the second adhesive layer independently include a silane coupling agent grafted modified polymer or a maleic anhydride grafted modified polymer; Preferably, the melting points of the silane coupling agent grafted modified polymer or the maleic anhydride grafted modified polymer are independently 60 to 90°C.

3. The glass fiber composite packaging film according to claim 2, characterized in that: The silane coupling agent grafted modified polymer includes any one or a combination of at least two of a silane coupling agent grafted modified polyolefin elastomer, EPDM rubber, EPDM rubber, polyisobutylene, and amorphous α-olefin copolymer; Preferably, the silane coupling agent includes any one or a combination of at least two of mercaptosilane, epoxysilane, aminosilane, methacryloxysilane, vinylsilane and isocyanatesilane; Preferably, the maleic anhydride grafted modified polymer includes any one of maleic anhydride grafted modified polyolefin elastomer, EPDM rubber, EPDM rubber, polyisobutylene, and amorphous α-olefin copolymer, or a combination of at least two thereof.

4. The glass fiber composite packaging film according to claim 2 or 3, characterized in that: In the silane coupling agent graft-modified polymer or the maleic anhydride graft-modified polymer, the grafting rate of the silane coupling agent or maleic anhydride is independently 0.2-3%.

5. The glass fiber composite packaging film according to any one of claims 1 to 4, characterized in that: The second adhesive layer also includes a light stabilizer; Preferably, based on 100% of the total weight of the second adhesive layer, the content of the light stabilizer is 0-2.5%.

6. The glass fiber composite packaging film according to any one of claims 1 to 5, characterized in that: The structure of the glass fiber cloth in the middle layer is any one of plain weave, twill weave, satin weave, rib weave or basket weave, and the weight of the glass fiber cloth is 50-500 g / m 2 The monofilament diameter of the fiber material of the glass fiber cloth is 5 to 20 μm.

7. The glass fiber composite packaging film according to any one of claims 1 to 6, characterized in that: The thickness of the first adhesive layer is 10 to 150 μm; Preferably, the thickness of the intermediate layer is 150 to 450 μm; Preferably, the second adhesive layer has a thickness of 10 to 250 μm.

8. The glass fiber composite packaging film according to any one of claims 1 to 7, characterized in that: The transverse and longitudinal heat shrinkage rates of the glass fiber composite packaging film are both less than 5%; Preferably, the linear thermal expansion coefficient of the glass fiber composite packaging film in the thickness direction is less than 300 μm / (m·°C).

9. A method for preparing a glass fiber composite packaging film according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The grafted modified polymer is cast on both sides of the glass fiber cloth to obtain the glass fiber composite packaging adhesive film.

10. Use of the glass fiber composite packaging film according to any one of claims 1 to 8 in a perovskite battery.

Citation Information

Patent Citations

  • Method for regulating and controlling stress of perovskite thin film by using chemical cross-linking agent and perovskite solar cell

    CN113285031A

  • Perovskite-polymer composite material, preparation method and perovskite solar cell

    CN115528178A

  • Defect and stress regulating agent for FA1-xCsxPbBryI3-y perovskite thin film, regulating method and application

    CN116406212A